Structural origins for the generation of strength, ductility and toughness in bulk-metallic glasses using hydrogen microalloying. (1st June 2019) - Luo, L.S.; Wang, B.B.; Dong, F.Y.; Su, Y.Q.; Guo, E.Y.; Xu, Y.J.; Wang, M.Y.; Wang, L.; Yu, J.X.; Ritchie, R.O.; Guo, J.J.; Fu, H.Z.
Abstract: A vital requirement for bulk-metallic glasses (BMGs) as structural materials is the attainment of both strength and toughness, yet invariably, as in most materials, these properties are mutually exclusive. However, by utilizing a hydrogen microalloying technology, involving alloying with a gas mixture of hydrogen/argon, we have converted "strong-yet-brittle" bulk-metallic glasses into "stronger-and-tough" ones. We combine experiments with molecular dynamics simulations to systematically analyze the atomic-scale details on how trace hydrogen additions can induce internal changes in the amorphous structure of Zr-Cu-based glassy alloys, with the aim of discerning the structural origin of the combined high strength, ductility and toughness of these materials. Our results, from both relaxation spectrum analysis and calculations of the atomic configurations, indicate that minor additions of hydrogen, instead of causing embrittlement, can have a positive influence on the mechanical properties of BMGs. Specifically, they generate more highly activated "soft spots" to promote multiple shear bands to enhance deformability, yet at the same time engender the formation of a more strengthened structural matrix to delay their initiation, a factor which can serve to elevate strength. Accordingly, our H-alloyed samples display a larger yield strength and fracture strain than the H-free ones. The current findings not only show how the strength-toughness trade-off can be successfully overcome in bulk-metallic glasses, but also we regard this understanding as a step forward to decoding the salient underlying mechanisms for the correlating structure, relaxation behavior and mechanical properties of these materials. Graphical abstract: Image 1